Functional Response of Predator Paederus sp. (Coleoptera: Staphylinidae) - Astrid Sri Wahyuni Sumah (Universitas Djuanda, 2023)
Research on predatory predation of Paederus sp. (Coleoptera: Staphylinidae) was carried out to study the functional response of the predator Paederus sp. Functional response is a form and size predictor of consumer impact on resource populations, determining the effectiveness of a predator as an agent in biological control. Predation time in hungry and not-hungry conditions influences predator-prey interactions, which are essential in functional response. The method used in predating Paederus sp. on the prey of aphids was Aphid spp. They are using four levels of prey density with two different predator treatments. The results show the functional response model of Paederus sp. predators. against the prey of Aphid spp. Described in a type II model. The level of predation of Paederus sp. showed different results for the two treatments and an increasing cystoid curve at a rising rate. The level of predation is still increasing, along with the increase in host density, and can be a starting point for controlling the Aphid spp and using predators Paederus sp. in the field.